MSMEs Marketplace Application Design "NUTREAZY": Food Delivery Service Based on Nutrition Optimization - Moch Panji Agung Saputra; Muhammad Herlambang Prakasa Yudha; Faizal FaMusthofa; Ahmad Ihsan Fathurrizki (International Journal of Research in Community Services, 2021)
NUTREAZY is a marketplace application that provides food delivery service with complete nutritional information. This application can provide food menu recommendations based on optimization of nutritional fulfillment at the most optimal price. This marketplace application was created to provide solutions to the problems of food needs and intake in today's millennial era. Millennials tend to want food that is practical, easy to get, but at an affordable price. These habits make the millennial society's eating patterns become instantaneous. In addition, the role of the NUTREAZY application innovation is to increase the branding of quality MSME products and attract consumer buying interest. Delivery services can add value to the services of MSMEs while at the same time responding to the wishes of the millennial community with digital services that are easily available.